INTERMOLECULAR INTERACTION STUDIES OF METFORMIN HCl AND GLIMEPIRIDE MIXTURES AND EFFECT OF THE INTERACTION ON SOLUBILITY AND DISSOLUTION OF GLIMEPIRIDE - Raodah Nurul Jannah, Sitti
Intermolecular interaction between two active compounds could effect of physicochemical properties of the compounds. Identification of intermolecular interaction between glimepiride (GMP) and metformin HCl (MET) by fusion method, solid state grinding (SSG), solvent drop grinding (SDG) and solvent evaporation (SE) with ratio molar 1:1 had been carried out. The result of fusion method in methanol as a solvent shown new crystal habit of GMP-MET physical mixture as small tabular shaped which indicated an intermolecular interaction occured. Identification of GMP-MET mixture based on DTA/TG thermogram shown two new endotermic peaks corresponding to peritecticum at temperature 197,02 and 216,64 o C. Microscopic analysis by SEM of SE method showed the change of habit and morphology crystal to be a long tabular shaped. There are no new peaks found in PXRD and FTIR data. The solubility and dissolution of GMP after treatment increased by SSG, SDG and SE methods even from physical mixture in phosphate buffer medium pH 7.4. The highest solubility and dissolution values obtained from SDG method 0,041 mg/ml and 57,33% respectively.